Juvenile Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A young girl with recurrent episodes of CNS demyelination associated with defective mitochondrial beta oxidation is reported from the Departments of Pediatrics, Medical Genetics, Oregon Health Sciences University, Portland, and University of Iowa Hospitals, Iowa City, IA.